Qualitative inquiry and research design: Choosing among five traditions, John W. Creswell Los Ángeles: SAGE, 2013 (Estudios de la Gestión: Revista Internacional de Administración, 2020)
Qualitative inquiry and research design: Choosing among five traditionsJohn W. Creswell, Los Ángeles: SAGE, 2013